INDUNG PADA WADITRA KACAPI - Maulina, Rini (Visualita Jurnal Online Desain Komunikasi Visual, 2019)
Indung is a Sundanese word. The word in Indonesian and English means mother. The word Indung is found in Sundanese cultural artifacts, one of which is in the waditra, a Sundanese traditional musical instrument, for example in the waditra Kacapi called Kacapi Indung. This research is a pre-research that uses library research methods and aims to know Indung as a symbol of Sundanese culture, by conducting a study on Kacapi Indung and the theories used are psychoanalysis and culture. Analysis of Indung with the use of these theories indicates that the existence of Indung is present in all categories made by experts and shows significant suitability.